Voltage feasibility-constrained peer-to-peer energy trading with polytopic injection domains - Sampath, Lahanda Purage Mohasha Isuru (2022)
Peer-to-peer (P2P) energy trading is an important energy market concept that improves the utilization of distributed energy resources and promotes the integration of energy storage technologies in distribution grids. It is challenging to satisfy the grid operational feasibility under such decentralized energy markets while enabling fully autonomous prosumer operations. This work develops a self-validation mechanism based on polytopic injection domains that define the allowed/safe region of prosumer power injections, ensuring feasible operation of the distribution grid. The allowed polytopic injection domains are constructed effectively by leveraging a newly developed feasibility criterion based on Kantorovich's fixed-point theorem. Therewith, we design a novel P2P energy market framework supporting the autonomous participation of prosumers and propose a nodal aggregator model to validate the aggregated prosumer power injections to attest a voltage-feasible market-clearing.